ANALISIS DAMPAK PENINGKATAN KOMPETENSI DAN KINERJA GURU MELALUI PROGRAM BERMUTU TERHADAP KEGIATAN MGMP DI KABUPATEN PARIGI MOUTONG - Rus'an Rus'an (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
This study aims to knows the Impact of Competence Improvement and Teacher Performance through BERMUTU Program for MGMP in Parigi Moutong Regency. The method used is the qualitative approach, further to obtain the data in accordance with the problems, techniques of data collection is done by observation, interviews, questionnaires, and documentation. The results showed that the respondents teacher Overall performance has been categorized as good, but specifically in the learning assessment components still need to be improved. The predicted performance of teachers is the impact of the activities of teachers in the working group. Where there has been shared their experiences and discuss and develop a collective lesson preparation. Average appearance of teaching junior high school teacher conducting PKB (Sustainable Profession Improvement) on MGMPs recipient of the Direct Assistance Fund is 3.12 BERMUTU program with good category. The sub-components of teaching that need attention for each group of teachers, namely: 1) Teacher of Indonesian language in assessment component; 2) Teachers of English in planning and assessment component; 3) Teachers of Mathematics in planning and assessment component; 4) Teachers of science in assessment component